Avanço histórico e tecnológico da representação descritiva: do AACR ao RDA - Taveira, Djaine Xavier (2019)
We live in the Age of Knowledge, where changes occur in technologies and consequently in documents and their media. Faced with so many revolutions throughout the history of books and libraries, such as the Press Revolution, the Industrial Revolution and now the Information Revolution, there must be a revolution in making librarians so that information can continue to be treated, made available and achieved these days. The present work aims to outline the evolution of cataloging, recognizing the importance of the RDA in contemporaneity. It will determine the degree of importance of the descriptive representation, as well as present the characteristics of the RDA standard. Specifically, a historical survey was carried out on Information Representation, recognizing its practices, support and techniques used to date. The methodology used is the bibliographical survey on the development of cataloging; Brief history of catalogs; and Resources: Description and Access - RDA, the research method being totally deductive. Finally, it is noticed that the evolution of the cataloging is totally focused on the needs of the users. The techniques and support used to support all informational content changes according to the needs of users of such information.